Pengaruh Pemahaman Agama Islam Terhadap Pembentukan Pedoman Hidup Seorang Muslim - Muhammad Mujani; Rabiatul Rabiatul; Aulia Wardani (PT Barkah Ilmi Fiddunya, 2024)
This study discusses how Islam as a comprehensive religion offers guidelines for life that not only regulate spiritual aspects, but also social, economic, and cultural aspects. In facing the changes that continue to occur in life, both at the individual and societal levels, Islam provides basic principles that can be used as a foundation for navigating the challenges of the times. The purpose of this study is to provide insight for Muslims so that they can make Islam a solid guideline in facing all forms of change, both in personal and social aspects of life. The method used in this study is a qualitative method, by using books, magazines, articles and journals related to the research theme to collect data, then codify it, and then describe it in this article. The results of this study indicate that Islam emphasizes the importance of steadfastness to the basic principles contained in the Qur'an and Hadith, which have not changed over time. These principles include justice, compassion, moral integrity, and self-development through knowledge and worship. This understanding is expected to strengthen the spiritual, moral, and social resilience of Muslims in an increasingly complex and global life.